Evolution of dike opening during the March 2011 Kamoamoa fissure eruption, Kīlauea Volcano, Hawai`i. Issue 3 (27th March 2013) - Lundgren, Paul; Poland, Michael; Miklius, Asta; Orr, Tim; Yun, Sang‐Ho; Fielding, Eric; Liu, Zhen; Tanaka, Akiko; Szeliga, Walter; Hensley, Scott; Owen, Susan
Abstract: [1] The 5–9 March 2011 Kamoamoa fissure eruption along the east rift zone of Kīlauea Volcano, Hawai`i, followed months of pronounced inflation at Kīlauea summit. We examine dike opening during and after the eruption using a comprehensive interferometric synthetic aperture radar (InSAR) data set in combination with continuous GPS data. We solve for distributed dike displacements using a whole Kīlauea model with dilating rift zones and possibly a deep décollement. Modeled surface dike opening increased from nearly 1.5 m to over 2.8 m from the first day to the end of the eruption, in agreement with field observations of surface fracturing. Surface dike opening ceased following the eruption, but subsurface opening in the dike continued into May 2011. Dike volumes increased from 15, to 16, to 21 million cubic meters (MCM) after the first day, eruption end, and 2 months following, respectively. Dike shape is distinctive, with a main limb plunging from the surface to 2–3 km depth in the up‐rift direction toward Kīlauea's summit, and a lesser projection extending in the down‐rift direction toward Pu`u `Ō`ō at 2 km depth. Volume losses beneath Kīlauea summit (1.7 MCM) and Pu`u `Ō`ō (5.6 MCM) crater, relative to dike plus erupted volume (18.3 MCM), yield a dike to source volume ratio of 2.5 that is in the range expected for compressible magma without requiring additional sources. Inflation of Kīlauea's summit in the months before the March 2011 eruption suggests that the Kamoamoa eruption resulted from overpressure of the volcano's magmatic system. Key Points: Detailed imaging of dike growth during eruption Dike volume increased during and in the two months following the eruption dike to source volume ratio does not require extra sources